(untitled) (Construction Economics and Building, 2013)
Construction firms in regional areas face considerable challenges to their competitiveness. Logistics, availability of suitable personnel, unfamiliarity with trading partners, and the tyranny of distance conspire to obstruct profitable engagement beyond their local area. Electronic information and communication technology (ICT) such as web-based project management applications and other forms of collaborative data sharing have the potential to mitigate many of these obstacles, but have yet to gain widespread acceptance, particularly by smaller regional firms who question their cost effectiveness. The attitudes of decision-makers and the impact of their decisions on intra- and inter-firm culture lie at the heart of ICT-mediated innovation. This paper presents a case study of a specialist subcontractor located in regional New South Wales and its involvement in a New Zealand project, whose competitiveness arose from using ICT to integrate its own supply chain. It also provided additional value by triggering collaboration and integration in the broader project team. The case reveals that these outcomes were symptomatic of the organisational culture of the subcontractor, and were achieved through a combination of leadership, collaboration, flexibility and pragmatism, redolent of dynamic capabilities.